Gambaran Perilaku Self Diagnosis Dan Tingkat Literasi Kesehatan Masyarakat Usia 18-44 Tahun Di Wilayah Tataaran 1 - Junita Winni Palondongan (STIKES Columbia Asia Medan, 2026)
The development of information technology has driven an increase in self-diagnosis behavior, especially among the productive-age population with broad access to the Internet. This phenomenon has the potential to result in inaccurate health assessments and influence health-related decision making. This study aimed to describe self-diagnosis behavior, motivations, patterns of seeking health information online, consequences after performing self-diagnosis, and the level of health literacy among people aged 18-44 in the Tataran 1 area. This research uses a quantitative descriptive design with a survey method through questionnaires given to 60 respondents in the company. The results show that the majority of respondents are female, aged 35-44, and have a high school level education. Some respondents were not motivated to perform self-diagnosis, and the level of seeking health information online was considered low to moderate. Nevertheless, nearly half of the respondents still took follow-up actions after performing self-diagnosis. The majority of respondents had a moderate level of health literacy, so the ability to understand and evaluate health information still needs to be improved. These findings underscore the importance of digital health literacy education so that the public can accurately sort medical information and reduce the risk of mistreatment due to self-diagnosis of the disease.